Gender Dimension Of Waves Of Democratization: Abortion And Reproductive Right Between Eastern And Western Europe - Desperak, Iza (European Scientific Journal, ESJ, 2016)
This paper focuses on the gender dimension of the transition processes of Western and Eastern Europe, which is viewed from the perspective of democratization processes, i. e. waves of democratization. Adding gender perspective to the analysis, results in the reconceptualization of the democratic approach to the transitional processes. As proposed by Charles Tilly, it requires an alternative approach such as de-democratisation. Some examples of countries with a chosen Western and Eastern European transitions system include: Spain, Portugal, Poland, and Romania. During the last fifty years, they showed how politics concerning reproductive rights, especially on the issue of abortion, differentiate between the real shape and the direction of transition processes which leads either to democratization or its complete opposite.